Climatic data acquisition system for satellite communications - Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed; Dao, Hassan (2010)
Several climatic dynamic phenomena such as rain and turbulence can seriously affect the quality of satellite communications. This project presents the design and implementation of a data acquisition system. The system provides accurate vital information to facilitate proper analysis of anticipated problems so that solutions can be incorporated when designing earth-satellite systems. Signals from the beacon of MEASAT3 located at 91.5ËšE orbit is received by a 2.4 meter Parabolic dish. The signal is measured in real-time by a Spectrum Analyzer using a General Purpose Interface Bus (GPIB) cable which provides high speed transmission. The system is equipped with a synchronized 0.2mm tipping bucket rain gauge. For data logging and analysis a system was developed using LabView version 8.6. The logging process involves data recording every 0.1 second.